IDENTIFIKASI SENYAWA KIMIA DAN AKTIVITAS ANTIBAKTERI EKSTRAK Piper Sp. ASAL PAPUA - Priyono, Sumarnie; Praptiwi, Praptiwi (Jurnal Teknologi Lingkungan, 2009)
The aim of this study was to identity the chemical compounds of the piper sp.Fruit originated from Papua, that has been used as Ã¢â‚¬Å“sirih pinangÃ¢â‚¬Â(chew betle)and to determine the antibacterial activity of hexane and chloroform extraxt ofpiper sp. to Gram + bacteria isolates(Bacillus subtilis, Listeria monocytogenesdan Staphylococcus aureus) and Gram Ã¢â‚¬â€œ bacteria isolates(Salmonellatyphimurium, Eschericia coli and Pseudomonas pseudomallei). The extractconcentration were 50 % and 25 %, and every treatment consisted of 3replications. The bacteriae growth media was Mueller Hinton Agar(MHA). Theresult of phytochemical screening of Piper sp.fruit(ether, alcohol,and waterextracts)showed that it contained esential oil, lipid,emodol,tannin,reducingsugar, anthrasenoid,polyuronide,glucocide,steroid glycoside.